Exploring the impact of ketogenic diet on multiple sclerosis: obesity, anxiety, depression, and the glutamate system - Ortí, Jose Enrique de la Rubia; Cuerda-Ballester, María; Sanchis-Sanchis, Claudia Emmanuela; Lajara Romance, Jose María; Navarro-Illana, Esther; García Pardo, María Pilar (Frontiers in Nutrition, 2023)
Background: Multiple sclerosis (MS) is a neurodegenerative disorder characterized by functional disability, obesity and the presence of anxiety and depression. Axonal demyelination can be observed and implies alterations in mitochondrial activity and increased inflammation associated with disruptions in glutamate neurotransmitter activity. In this context, the ketogenic diet (KD), which promotes the production of ketone bodies in the blood (mainly β-hydroxybutyrate (βHB)), is a non-pharmacological therapeutic alternative that has shown promising results in peripheral obesity reduction and central inflammation reduction. However, the association of this type of diet with emotional symptoms through the modulation of glutamate activity in MS patients remains unknown. Aim: to provide an update on the topic and discuss the potential impact of KD on anxiety and depression through the modulation of glutamate activity in patients with MS. Discussion: the main findings suggest that the KD, as a source of ketone bodies in the blood, improves glutamate activity by reducing obesity, which is associated with insulin resistance and dyslipidemia, promoting central inflammation (particularly through an increase in interleukins IL-1β, IL-6, and IL-17). This improvement would imply a decrease in extrasynaptic glutamate activity, which has been linked to functional disability and the presence of emotional disorders such as anxiety and depression.